Cultural Narratives in Motion: New Farmers’ Short Videos and the Rural Revitalization - Yu, Yanshen; Liang, Haolan; Jian, Xiaoqi; Yin, Hang; Yang, Chujun (Journal of Global Economy, Business and Finance, 2025)
Rural revitalization in China has increasingly relied on digital media to reconfigure cultural expression, social participation, and local identity. However, existing research has seldom examined how new farmers employ short-video storytelling to reconstruct cultural meanings and moral frameworks in everyday rural life. Drawing on qualitative thematic analysis of new farmers’ short videos on Douyin (the Chinese version of TikTok), this study investigates how digital narratives function as affective, cultural, and moral infrastructures that connect everyday life with broader ideological and policy frameworks. The findings suggest that new farmers’ cultural narratives transform ordinary labor and interaction into symbolic performances of virtue, continuity, and belonging, as a result, turning rural life into a living archive of moral and aesthetic renewal. By highlighting how affective storytelling revitalizes moral tradition and strengthens communal cohesion, this study could contribute to the sociology of digital culture and offer practical insights into leveraging digital participation for sustainable rural revitalization.